Strategi Penguatan Administrasi Kependudukan dalam Mendukung Program Bangga Kencana untuk Pembangunan Berkelanjutan di Indonesia - Hamid, Syaifa Azurra; Syamsir; Diva Tri Delviyanti; Tasya Rudinia Berty; Nur Hafizah Putri Indriani; Afifah Afra Amatullah; Nadila Rahma Cahyani (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze strategies for strengthening population administration in supporting the Bangga Kencana Program as part of efforts to achieve sustainable development in Indonesia. The research employed a systematic literature review using thematic and bibliometric analysis, complemented by an evaluation based on the Context, Input, Process, and Product (CIPP) framework to assess the effectiveness of population administration service innovations at both national and local levels. Data were collected from scholarly publications, official policy reports, and evaluations of digital technology implementation, including the Self-Service Population Administration Kiosk (ADM), Village Information Systems (SIDESA), and other digital-based population service platforms. The findings indicate that the effectiveness of strengthening population administration is strongly influenced by regulatory readiness, human resource capacity, and the availability of digital infrastructure. Technology-based service innovations have been shown to improve efficiency, transparency, and service accessibility, with effectiveness increases ranging from 35–50% in regions with adequate input readiness. Furthermore, data integration and multi-stakeholder collaboration significantly contribute to expanding service coverage by up to 40%, particularly in remote areas. Nevertheless, several challenges remain, including infrastructure limitations, low levels of digital literacy among communities, and the need for continuous socialization and assistance. In conclusion, strengthening population administration constitutes a strategic element in supporting the Bangga Kencana Program and advancing sustainable development goals. Enhancing human resource capacity, reinforcing regulatory frameworks, and developing inclusive and integrated digital platforms are key recommendations for improving the effectiveness of population administration services in Indonesia.